2010
DOI: 10.1021/jp100104d
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Oxygen Vacancy Formation and Annihilation in Submonolayer Coverages of TiO2 Dispersed on MCM-48

Abstract: The reduction and reoxidation of submonolayer coverages of TiO2 deposited onto MCM-48 were investigated. The deposited TiO2 was characterized by Raman and UV−visible spectroscopy. Raman spectra show that Ti atoms are bonded to the silica support by Ti−O−Si bonds and that crystalline TiO2 is not formed. The results of the Raman and UV−visible spectroscopy suggest that the dispersed TiO2 is present as two-dimensional oligomeric structures. Reduction in H2 at 923 K produces Ti3+ cations observable by EPR (g = 1.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
81
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 88 publications
11
81
1
1
Order By: Relevance
“…For sample (9) (Figure 7), two absorption bands can be clearly identified with peaks at 30,000 and 35,500 cm −1 . According to [17,18], these bands can be attributed to oxygen defects (O 2 − ), which may appear in the TiO 2 structure, depending on the method of sample synthesis. The analysis of the intensity of the absorption bands at 30,000, 35,500, and 12,700 cm −1 in the UV-Vis-DRS of all the samples showed that as the number of Ti 3+ cations with coordination numbers less than 6 increased, the number of oxygen defects (O 2 − ) in the titanium dioxide structure decreased.…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For sample (9) (Figure 7), two absorption bands can be clearly identified with peaks at 30,000 and 35,500 cm −1 . According to [17,18], these bands can be attributed to oxygen defects (O 2 − ), which may appear in the TiO 2 structure, depending on the method of sample synthesis. The analysis of the intensity of the absorption bands at 30,000, 35,500, and 12,700 cm −1 in the UV-Vis-DRS of all the samples showed that as the number of Ti 3+ cations with coordination numbers less than 6 increased, the number of oxygen defects (O 2 − ) in the titanium dioxide structure decreased.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…It is well known that TiO 2 is an indirect-gap semiconductor [18]. It is characterized by a fundamental absorption edge (or band gap, ).…”
Section: Optical Propertiesmentioning
confidence: 99%
“…In this study, the crystallization and electrical characteristics of Ni-doped LPD-TiO 2 films grown on p-type (100) silicon substrate were investigated. [17]. Moreover, LPD-TiO 2 has more concentration oxygen vacancy than that by other deposition methods (sol-gel, magnetron sputtering and metal organic chemical vapor deposition) due to high concentration of water molecules examined by FTIR in LPD-TiO 2 film [9].…”
Section: Introductionmentioning
confidence: 99%
“…Crystal steps and edges are important defect features in TiO 2 surfaces (Derdour and Skliar, 2012) and are involved in several processes, including nucleation of Au particles and adsorption of molecules. The relatively low density of point defects, such as surface oxygen vacancies on TiO 2 , which play an important role in catalytic oxidation (Strunk et al, 2010;Namai and Matsuoka, 2005), is also related to these perimeter sites (Fujitani and Nakamura, 2011). Both theoretical calculations and experimental results concerning the effects of oxygen vacancies in TiO 2 on catalytic reactions have been widely investigated.…”
Section: Introductionmentioning
confidence: 99%